Hubungan Kandungan Mineral Calcium, Magnesium, Mangaan Dalam Sumber Air Dengan Kejadian Batu Saluran Kemih Pada Penduduk Yang Tinggal di Kecamatan Songgom Kabupaten Brebes - Wahap, Sandy; Setiani, Onny; Joko, Tri (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2012)
Background : Urinary tract stones is a common urinary tract disease in the world and occurs primarily in peopleliving around the mining of limestone, or areas with high hardness of water. Based on the results of the types of water sources by the number of respondents who examined 34 samples showed that the calcium levels eâ€ 100 mg / liter of 4 people (11.8%), mangaan levels eâ€ 0.5 mg / liter of 15 people (44.1 %), whereas the Magnesium levels eâ€ 30 mg / liter of 14 people (41.2%).The purpose this study was to determine the association between mineral content of calcium , magnesium, mangaanin the water with the incidence of urinary tract stones on community the living in the karst area Songgom districBrebes regency.Methode : The study design was a case-control study. With the population of the whole community in SonggomBrebes regency. Sampling using random sampling techniques. The number of 68 people. Data obtained from interviews with respondents, and examination of urine and water resources.Result: The results showed there was a significant association between length of stay with the incidence of urinary tract stones with the results of statistical analysis stating the value of p = 0.015 and OR = 3.833 with 95% CI = 1.403 <OR <10.4770. There was a significant association between the consumption of water per day with the incidence of urinary tract stones with the results of statistical analysis showed that value of p = 0.028 and OR = 3.429 with 95% CI = 1.255 <OR <9.370. There was a significant association between levels of magnesium (Mg) with the incidence of urinary tract stones with the results of statistical analysis with value of p = 0.0001 and OR = 6.67 with 95% CI = 2.35 <OR <18.92.From the results of multivariate analysis, dominant variables as the cause of the incidence of urinary tract stones are long lived with the OR = 3.893, and the consumption of water per day with a value of OR = 3.487.Conclusion : The conclution of the research is concluded as the cause of occurrence of urinary tract stones is thelength of stay and the consumption of water per day.Key words : urinary tract stones, water resources, length of stay,Songgom distric.